Influence of Saline Fluids on the Electrical Conductivity of Olivine Aggregates at High Temperature and High Pressure and Its Geological Implications - Sun, Wenqing; Dai, Lidong; Hu, Haiying; Jiang, Jianjun; Wang, Mengqi; Hu, Ziming; Jing, Chenxin (Frontiers in Earth Science, 2021)
The electrical conductivities of hydrous olivine (Ol) aggregates and Ol–H2O, Ol–NaCl–H2O (salinity: 1–21 wt%; fluid fraction: 5.1–20.7 vol%), Ol–KCl–H2O (salinity: 5 wt%; fluid fraction: 10.9–14.0 vol%) and Ol–CaCl2–H2O systems (salinity: 5 wt%; fluid fraction: 10.7–13.7 vol%) were measured at 2.0–3.0 GPa and 773–1073 K using a multi-anvil apparatus. The electrical conductivity of saline fluid-bearing olivine aggregates slightly increases with increasing pressure and temperature, and the electrical conductivities of both hydrous and saline fluid-bearing samples are well described by an Arrhenius relation. The dihedral angle of the saline fluids is approximately 50° in the Ol–NaCl–H2O system with 5 wt% NaCl and 5.1 vol% fluids, which implies that the fluids were interconnected along grain boundaries under the test conditions. The electrical conductivities of the Ol–NaCl–H2O system with 5 wt% NaCl and 5.1 vol% fluids are ~2–4 orders of magnitude higher than those of hydrous olivine aggregates. The salinity and fluid fraction moderately enhance the sample electrical conductivities owing to the interconnectivity of the saline fluids. The activation enthalpies of the electrical conductivities for the Ol–NaCl–H2O systems range from 0.07 to 0.36 eV, and Na+, Cl−, H+, OH− and soluble ions from olivine are proposed to be the main charge carriers. For a fixed salinity and fluid fraction, the electrical conductivities of the Ol–NaCl–H2O system resemble the Ol–KCl–H2O system but are slightly higher than that of the Ol–CaCl2–H2O system. The Ol–NaCl–H2O system with a salinity of ~5 wt% NaCl and fluid fraction larger than 1.8 vol% can be employed to reasonably explain the origin of the high-conductivity anomalies observed in mantle wedges.